Accumulating physical activity in at least 10-minute bouts predicts better lung function after 3-years in adults with cystic fibrosis. Issue 2 (9th April 2018) - Cox, Narelle S.; Alison, Jennifer A.; Button, Brenda M.; Wilson, John W.; Morton, Judith M.; Holland, Anne E.
In people with cystic fibrosis (CF) reduced fitness and lower levels of physical activity have been associated with poorer prognosis [1] and greater decline in lung function [2]. Despite the health benefits of being physically active [3], in people with CF adherence to exercise programmes is often poor [4], and prescribed exercise training programmes have seldom translated into increased daily physical activity [5]. Achieving physical activity guidelines by undertaking multiple bouts of moderate-vigorous physical activity ≥10 min duration, but not shorter periods of activity, was independently associated with less decline in FEV 1 over 3 years among adults with CF http://ow.ly/yk6930ivCV8